Explainable Artificial Intelligence (XAI) (International Journal of Food and Nutritional Sciences, 2023)
Explainable Artificial Intelligence (XAI) has emerged as a critical facet in the realm ofmachine learning and artificial intelligence, responding to the increasing complexity ofmodels, particularly deep neural networks, and the subsequent need for transparent decisionmaking processes.